2007
DOI: 10.1016/j.ymgme.2007.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow transplantation for feline mucopolysaccharidosis I

Abstract: Severe mucopolysaccharidosis type I (MPS I) is a fatal neuropathic lysosomal storage disorder with significant skeletal involvement. Treatment involves bone marrow transplantation (BMT), and although effective, is suboptimal, due to treatment sequelae and residual disease. Improved approaches will need to be tested in animal models and compared to BMT. Herein we report on bone marrow transplantation to treat feline mucopolysaccharidosis I (MPS I). Five MPS I stably engrafted kittens, transplanted with unfracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
25
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 34 publications
9
25
0
Order By: Relevance
“…Myocardial GAG storage and valve abnormalities similar to those of MPS I patients have previously been described in MPS I cats (19,21,27). We noted complete correction of storage lesions in myocardium and aorta of the three cats with stable serum IDUA activity, and moderate improvement in the animal with reduced serum IDUA activity (Fig.…”
Section: Resultssupporting
confidence: 52%
See 2 more Smart Citations
“…Myocardial GAG storage and valve abnormalities similar to those of MPS I patients have previously been described in MPS I cats (19,21,27). We noted complete correction of storage lesions in myocardium and aorta of the three cats with stable serum IDUA activity, and moderate improvement in the animal with reduced serum IDUA activity (Fig.…”
Section: Resultssupporting
confidence: 52%
“…MPS I cats carry a 3-bp in-frame deletion producing the omission of a single aspartate residue from the IDUA protein, resulting in a complete loss of catalytic activity (24). These animals exhibit GAG storage in most tissues and develop substantial orthopedic, corneal, and cardiac disease within the first 6 mo of life (19)(20)(21). We treated four MPS I cats between 3 and 5 mo of age (Table 1) with an i.v.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In these studies, animals were transplanted after the neonatal period, and in some of them, engraftment levels were suboptimal. 22,[31][32][33][34] MPS VII mice treated with BMT in neonatal life showed pathological and clinical improvements by clearing lysosomal storage in bones, joints, and visceral organs, even though engraftment achieved was low (15% to 20%). 16,17 To achieve a more complete donor-derived engraftment, we decided to use a busulfan-mediated preconditioning regimen, which was previously reported to result in high levels of hematopoietic engraftment after nBMT, and a complete hepatic correction in the erythropoietic protoporphyria mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…The life expectancy of MPS IH mice is between 12 and 17 months. Previous studies have observed accumulation of gangliosides GM3 and GM2 in Idua -/-mice, as well as in dog and cat MPS IH models, but detailed lipid analysis has not been performed in either mouse, cat, or dog [22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%